Usefulness of Carotid Ultrasonography in the Diagnosis of Coronary Artery Disease Patients - Tahir Hussain, Rafeah Khan, Muhammad Saqib Qamar Ishaqi, Syed M Shahnawaz Hyder, Manoj Kumar, Sheema Ihtisham (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The research aimed to examine whether the carotid condition is linked to coronary artery disease in sufferers sent to exercise echocardiography and when it raises the exercise echocardiography capability to forecast coronary artery disease. Place and Duration: During the last five years, continuous subjects over eighteen years with diagnosed coronary artery disease underwent exercise echocardiography and carotid ultrasound at Indus Hospital Karachi. Study Design: Cross-sectional Methodology: We studied 312 participants without past heart disease who experienced exercise echocardiography, coronary angiography, and carotid ultrasonography over five years. Specific variables had been described as proportions, and evaluation among groups was according to Fisher’s exact and chi-square tests. Constant variables had been described as mean or median whenever their distribution deceased from average, and variations had been evaluated through the un-paired t-test. Continuous and binary quantitative variables have been likened to utilizing binary logistic regression. IBM SPSS, Version 20 was utilized. Results: 178 (57.1 percent) participants had substantial coronary artery disease. Components linked to CAD in multi-variate evaluation were FPG (OR 2.04, p=0.062), pre-test possibility of CAD greater than 65 percent (odds ratio 7.42, p less than0.004), positive exercise echocardiography (odds ratio 42.04, p less than 0.004) and carotid plaque presence (odds ratio 5.8, p= 0.052). There wasn’t a statistical factor in the area below the curve after the inclusion of carotid plaque to exercise echocardiography results (3.08 vs. 3.24, p=1.05) nor the level of sensitivity, uniqueness, predictive efficiency, or values. Conclusion: Carotid plaque is linked to CAD in sufferers going through exercise echocardiography (EE), although its inclusion to EE doesn’t improve coronary artery disease (CAD) prediction, most likely because of inadequate mathematical power. Carotid plaque reclassified 1 / 3 of sufferers to high risk class in spite of negative exercise echocardiography (EE) or absence of coronary artery disease; these subjects take advantage of aggressive primary prevention treatments. Keywords: Carotid Ultrasonography, Coronary Artery Disease, echocardiography